Pilates method in fibromyalgia syndrome (Research, Society and Development, 2023)
The present article aims to address, through a narrative literature review, the relevance of the Pilates method for individuals dealing with fibromyalgia, with a special focus on symptom reduction and condition management, aiming to enhance their quality of life. This study is a narrative literature review adopting a qualitative approach. Data collection was conducted between March and October 2023, during which available studies in databases were examined. The following keywords were employed: "Pain," "Pilates," "Fibromyalgia," and "Quality of life." Fibromyalgia is a rheumatological condition characterized by chronic widespread pain, reduced pain threshold, hyperalgesia, and allodynia. The diagnosis of fibromyalgia is clinical and involves the identification of tender points on the body. Treatment is highly individualized and aims to control symptoms, improve quality of life, and minimize pain. It includes a combination of pharmacological and non-pharmacological treatments, such as physical activities, physiotherapy, and even the practice of the Pilates method. The combination of Pilates with physiotherapy has proven to be effective in treating fibromyalgia, providing improvements in the quality of life, pain relief, and functional reeducation. Physical activities like walking, Pilates, and swimming, when supervised by physiotherapists, contribute to pain relief, improved cardiorespiratory function, and muscle strengthening.